Zr-Ti getter film integration in MEMS vacuum packaging. (April 2023) - Lemettre, Sylvain; Bessouet, Clément; Aassime, Abdelhanin; Coste, Philippe; Bosseboeuf, Alain; Moulin, Johan
Abstract: Titanium, zirconium, and Zr-Ti alloy thin films were evaporated under UHV. AFM, TEM and SEM observations showed that grain size at the surface of the films varies with their thickness and composition. The single-metal films exhibit larger grain than alloy films. The highest density of grain boundaries is found for Zr-Ti film with a balanced content in Zr and Ti. For the three types of films, the grain boundary density at the surface decreases when increasing the film thickness. The gettering properties of the films were studied by activation annealing in the range of 200 °C–400 °C by in situ sheet resistance monitoring and by integrating them into MEMS packages sealed at 300 °C. In both cases, the sorption of gases was found to increase with the surface density of grain boundaries. In the specific activation conditions of MEMS packaging, it is shown that reducing the film thickness from 400 nm to 50 nm enhances gas sorption by the Zr-Ti getter and for the first time, the activation of a getter film thinner than 100 nm integrated in a MEMS package was demonstrated. Highlights: The single-metal films Zr and Ti have a lower grain boundary density than the Zr-Ti alloy films. The higher grain boundary density is found for a Zr-Ti film having a balanced content in Zr and Ti. Zr, Ti and Zr-Ti films exhibit a grain boundary density at the surface that decreases with film growth. The film gas sorption is correlated with its surface grain boundary density. Reducing the Zr-Ti getter film thickness from 400 nm to 50 nm can enhance its gas sorption capability.